2019
DOI: 10.1101/524173
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microbial predictors of environmental perturbations in coral reef ecosystems

Abstract: 22times less affected by the environment and their community assembly patterns were 34 generally less uniform. Further, seawater microbial community data provided an 35 accurate prediction on the environmental state, highlighting the diagnostic value of 36 microorganisms and illustrating how long-term coral reef monitoring initiatives could 37 be enhanced by incorporating assessments of microbial communities in seawater. 38

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 75 publications
0
25
0
Order By: Relevance
“…Microbial communities associated with corals are continually exposed to fluctuations in the surrounding environment and the physiology of their host. Previous studies have demonstrated changes in the coral microbiome in response to thermal stress (Ainsworth & Hoegh-Guldberg, 2009;Grottoli et al, 2018;Lee et al, 2015;Thurber et al, 2009), ocean acidification (Grottoli et al, 2018;Thurber et al, 2009), organic matter enrichment (Garren & Azam, 2012), bleaching events (Bourne et al, 2008) and other environmental and physiological factors (Glasl et al, 2019a;Guppy & Bythell, 2006;Kelly et al, 2014;Li et al, 2015;Pollock et al, 2018). However, the coral microbiome is not homogenous across the animal and an improved understanding of the sensitivity of the microorganisms inhabiting each coral compartment is needed.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Microbial communities associated with corals are continually exposed to fluctuations in the surrounding environment and the physiology of their host. Previous studies have demonstrated changes in the coral microbiome in response to thermal stress (Ainsworth & Hoegh-Guldberg, 2009;Grottoli et al, 2018;Lee et al, 2015;Thurber et al, 2009), ocean acidification (Grottoli et al, 2018;Thurber et al, 2009), organic matter enrichment (Garren & Azam, 2012), bleaching events (Bourne et al, 2008) and other environmental and physiological factors (Glasl et al, 2019a;Guppy & Bythell, 2006;Kelly et al, 2014;Li et al, 2015;Pollock et al, 2018). However, the coral microbiome is not homogenous across the animal and an improved understanding of the sensitivity of the microorganisms inhabiting each coral compartment is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Manuscript to be reviewed Samples (n = 3 per sample type and per sampling event) for molecular analysis were collected as part of the Australian Microbiome Initiative and the sample procedure has previously been outlined by Glasl et al (2019a). In brief, coral nubbins (approximately cm tall) of both Acropora species were collected, rinsed with 0.2 µm filter-sterilized seawater and placed into cryogenic vials.…”
Section: Sample Collectionmentioning
confidence: 99%
See 3 more Smart Citations